Murine model for chronic rhinosinusitis: an interventional study - Amr F. Hamour; John JW. Lee; Ewa Wasilewski; Eric Monteiro; John M. Lee; Allan Vescan; Lakshmi P. Kotra (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Chronic rhinosinusitis (CRS) is a complex inflammatory disease of the sinonasal tract. To understand this disease entity and develop targeted treatments, a reproducible animal model is paramount. Aims/objectives To optimize a murine model of eosinophilic CRS by establishing benchmark histological markers and validate its fidelity in evaluating intranasal treatments. Material and methods Forty-five Balb/c mice were included in the 7-week protocol. Experimental animals (n = 20) were induced a CRS disease state upon receiving intraperitoneal sensitization with ovalbumin (OVA), followed by intranasal OVA with Aspergillus oryzae protease. Analysis of complete blood count with differential, peripheral blood smear, and histological markers from the nasal cavity mucosa were performed. CRS mice were additionally treated with intranasal saline (n = 5) or mometasone (n = 10) and compared with control groups of untreated CRS (n = 5) and healthy (n = 5) mice after week 7. Results Histological analysis of experimental animal nasal mucosa revealed significantly higher levels of eosinophilic tissue infiltration/degranulation, hyaline droplets, Charcot–Leyden crystals, and respiratory epithelial thickness compared to healthy controls. Treatment with mometasone significantly reversed the histopathological changes observed in CRS mice. Conclusion and significance This murine model induced substantial local eosinophilic inflammation within sinonasal mucosa, that was reversible with mometasone. This model may be used to evaluate the efficacy of therapeutics designed to target CRS.